Identification and functional analysis of drosophila mothers against decapentaplegic protein gene 1 (Smad1) from the red swamp crayfish Procambarus clarkii: The first evidence of Smad1 involved in immunity in invertebrates. Issue 127 (August 2022) - Zhang, Yan-Mei; Xu, Wen-Bin; Li, Bang-Ze; Lin, Chen-Yang; Cheng, Yuan-Xin; Xiao, Yi; Chen, Da-Yong; Dong, Wei-Ren; Shu, Miao-An
Abstract: Smads, part of signaling cascades that represent downstream pathways of the TGF-β super family proteins, are pleiotropic cytokines with important role in mediating cell proliferation, homeostasis, differentiation, apoptosis and immune response. However, the specific functions of Smads remain unknown in crustaceans. In the present study, the drosophila mothers against decapentaplegic protein gene 1 (Smad1) was firstly identified and characterized from the Red Swamp Crayfish Procambarus clarkii . The obtained cDNA sequence of pc Smad1was 2, 503 bp long with a 1, 488 bp open reading fame, which encoded a putative protein of 496 amino acids. Furthermore, pc Smad1 responded to both Aeromonas hydrophila and WSSV challenge, suggesting the involvement of pc Smad1 in innate immune responses. Knockdown of pc Smad1 in vivo dramatically increased the expressions of NF-κB signaling genes and anti-lipopolysaccharide factor genes. Additionally, overexpression of pc Smad1 in HEK293T cells could markedly activate NF-κB signaling. Taken together, these results indicated that pc Smad1 played an immune-regulatory role in crayfish's innate immunity, which may provide a better understanding of TGF-β superfamily members in crustacean. Highlights: Smad1 gene was firstly identified and characterized in crustacean species. Smad1 responded to both Aeromonas hydrophila and WSSV challenges. Smad1 contributed to innate immunity by regulating NF-κB signaling.